Desenho geométrico e geometria: análise dos livros didáticos de matemática do ensino fundamental II 1970 - 2000 - Queiroz, José Carlos Santana (2010)
This work makes a study showing the intrinsic relationship between the geometric design and geometry in the history of humanity and as they were of fundamental importance for the development of science, influencing various sectors of society. Because of the prestige achieved by these areas of study, there was a need to study in educational institutions and to achieve this goal, the textbook was his instrument. In Brazil, the first studies of geometry and geometric design were related to the construction of forts and weapons to defend the colony. Upon reaching the schools, due to European influences, the approach that was given to geometry in the textbooks included the geometric design. With the education reform of 1930, the geometry approaches a deductive presentation and geometric design became an independent discipline and binding. With the movement of Modern Mathematics in 1960 and the LDB of 1971, the geometry has been considered an irrelevant subject, so its inclusion in mathematics textbooks intended the last pages with a packed presentation and geometric design has become a discipline. However, the LDB of 1996 and the NCP in mathematics (1997), emphasized the necessity and importance of studying the geometry and that such an approach in the geometric design were included. This research examined how the geometric design was included in the approach given the geometry of two mathematics textbooks used in the 8th grade II, and an edited half of dedada 1970, MATHEMATIC Orlando Antonio Zambuzzi and another in the late 1990s, THE CONQUEST OF MATHEMATIC Ruy José Giovanni, Benedito Ruy José Giovanni Castrucci and Junior. The results indicate that the math textbook published in the 1970s incorporated the trends of the modern education proposals and the LDB of 1971 and the other book has added some indication of the new LDB and the suggestions of the NCP in math, but even so the camouflaged geometric design is becoming part of the exercises of the approach.